UNVEILING THE SHADOWLANDS: UNRAVELING THE COMPLEXITIES OF ILLICIT DRUG TRAFFICKING IN SOUTHEAST ASIA - Himawan, Ludy (Jurnal Hukum Progresif, 2024)
The illicit drug trade continues to pose a significant risk in Southeast Asia because of its widespread impact, which can be seen in the lives of millions of people. Drugs are addictive and can have a negative impact on the physical and mental health of users if misused. In order to break free from the grip of this seedy underworld, it is essential to have regional collaboration, public awareness, and comprehensive approaches that target the underlying reasons for both the demand for and supply of drugs. This paper aims to show the dynamics of illicit drug trafficking in Southeast Asian countries. The main focus of this paper is to provide a brief overview of the current situation of illegal drug trade in the Southeast Asian region.